Perkembangan dan Kontribusi Alumni Mesir Terhadap Pendidikan di Indonesia - Nawazir, Safrudin; Iswantir, Iswantir (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the development and contribution of Egyptian alumni to education in Indonesia. The method used in this research is research library (literature review). The results of the study show that: 1) Al-Azhar Egyptian alumni in various regions have a culturalist, synergistic, active, participatory and sustainable role, 2) There is a balanced continuity as indicated by the collaboration between the roles of